The Influence of Competence, Motivation and Work Discipline on Employee Performance at Al-Ghifari University Bandung. - Nurhadi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The aim of this research is to investigate the impact of competence, motivation, and work discipline on employee performance at Universitas Al-Ghifari. The urgency and significance of this study lie in enhancing human resource management to improve organizational effectiveness. This research employs a quantitative approach using a case study method. Data were collected through surveys distributed to 72 employees, followed by statistical analysis using multiple regression techniques. The results reveal that competence, motivation, and work discipline significantly influence employee performance both individually and simultaneously. Recommendations include implementing regular knowledge transfer programs to maintain high performance levels, providing incentives and continuous education to enhance motivation, and fostering a conducive work environment to uphold discipline and integrity